Płeć reportażu herstorycznego. Wprowadzenie w problematykę gatunku - Szewczyk, Joanna (Zagadnienia Rodzajów Literackich, 2024)
The subject of the article is herstorical reportage as a kind of unconventional approach to the past and one of the manifestations of the herstorical turn in the Polish humanities and contemporary literary field. The author analyzes the reasons for the growing popularity of the genre, related, among other things, to the memory turn and the demand for popular historical literature. The author attempts to characterize the poetics of herstorical reportage as a “blurred genre” and points out its connections with historical micro-writing and feminist criticism. Among other things, she points to the subjectivization of the author’s commentary, the inspiration of oral history, the disclosure of the reporter’s craft by reporting on the difficulties of finding documents and adding witnesses as distinguishing features of the genre. The author draws attention to the importance of the analytical category of gender for herstorical reportage, which makes it possible to reflect on cultural patterns of femininity and masculinity, their role in the formation of national identity, and to study gender-differentiated historical experience. The article analyzes the reportages of Marta Dzido, Olga Wiechnik, Marta Madejska and Joanna Kuciel-Frydryszak with a particular focus on their narrative strategies and the location of the female reporter subject. The purpose of the article is to show the genre of herstorical reportage as an important element of engaged humanities and a remedy for the “gender blindness” of conventional historiography.